2017
DOI: 10.1038/srep39889
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Human Umbilical Cord-Derived Mesenchymal Stem Cells in Acute Lung Injury Mice

Abstract: The incidence and mortality of acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) are still very high, but stem cells show some promise for its treatment. Here we found that intratracheal administration of human umbilical cord-mesenchymal stem cells (UC-MSCs) significantly improved survival and attenuated the lung inflammation in lipopolysaccharide (LPS)-induced ALI mice. We also used the proteins-chip and bioinformatics to analyze interactions between UC-MSCs treatment and immune-response alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 46 publications
5
87
0
Order By: Relevance
“…In a recent report, MSCs were intratracheally administrated into mice with an acute lung injury that caused inflammation. These MSCs demonstrated an inhibition of the inflammatory response of the macrophages by secreting prostaglandin‐E2, granulocyte‐macrophage colony‐stimulating factor (GM‐CSF), interleukin 6 (IL‐6), and interleukin 13 (IL‐13) and showed improvement in the diseased lungs (Zhu et al, ). Together, these new developments in the field of regenerative medicine have provided stimulus for the use of MSCs in clinical studies.…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent report, MSCs were intratracheally administrated into mice with an acute lung injury that caused inflammation. These MSCs demonstrated an inhibition of the inflammatory response of the macrophages by secreting prostaglandin‐E2, granulocyte‐macrophage colony‐stimulating factor (GM‐CSF), interleukin 6 (IL‐6), and interleukin 13 (IL‐13) and showed improvement in the diseased lungs (Zhu et al, ). Together, these new developments in the field of regenerative medicine have provided stimulus for the use of MSCs in clinical studies.…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
“…Results with * p ≤ .05, ** p ≤ .01 were considered statistically significant [Colour figure can be viewed at wileyonlinelibrary.com] an acute lung injury that caused inflammation. These MSCs demonstrated an inhibition of the inflammatory response of the macrophages by secreting prostaglandin-E2, granulocyte-macrophage colonystimulating factor (GM-CSF), interleukin 6 (IL-6), and interleukin 13 (IL-13) and showed improvement in the diseased lungs(Zhu et al, 2017). Together, these new developments in the field of regenerative medicine have provided stimulus for the use of MSCs in clinical studies.Currently, there are over 800 MSC-based clinical trials in the United States(ClinicalTrials.gov, 2017).…”
mentioning
confidence: 98%
“…The differentiation power of these cells in vivo and in vitro has led them to be considered as a good tool for regenerative medicine and tissue engineering. With regard to the high proliferation and the ability MSCs differentiation and also because their prominent role in the effects of immune modulation, the ability to migrate to injury sites, the secretion of growth factors, anti-inflammatory cytokines, extracellular vesicles as well as action through differentiation and cell-cell junction [19,20,27,28] can be used as an applied tool for the purpose of cell therapy for the treatment of congenital disorders, degenerative diseases, autoimmune diseases and also as efficient carriers to deliver treatment to specific areas [15,29].…”
Section: Mesenchymal Stem/stromal Cellsmentioning
confidence: 99%
“…The stem cell therapy is a developing area of intervention to control the disease by treating with specific stem cell markers to an individual. The in vivo experiment on mouse model showed that the administration of human umbilical cordmesenchymal stem cells (UC-MSCs) results in the modulation of inflammatory markers for the survival of the epithelail cell [5]. The mesenchymal stem cells (MSCs) demonstrated the potential therapy in lung diseases [5,6].…”
Section: Stem Cell Therapies For Lung Injurymentioning
confidence: 99%
“…The in vivo experiment on mouse model showed that the administration of human umbilical cordmesenchymal stem cells (UC-MSCs) results in the modulation of inflammatory markers for the survival of the epithelail cell [5]. The mesenchymal stem cells (MSCs) demonstrated the potential therapy in lung diseases [5,6]. These MSCs may collect from the umbilical cord (UC), adipose tissue, bone marrow, skeletal muscle and other tissues.…”
Section: Stem Cell Therapies For Lung Injurymentioning
confidence: 99%